Solution of Eighth Order Boundary Value Problems Using Differential Transformation Technique - Merna Samarchi (Al-Rafidain Journal of Computer Sciences and Mathematics, 2010)
In this paper we have applied the Differential Transform Method (DTM) for solving eighth-order boundary value problems. The analytical and numerical results of the equations have been obtained in terms of convergent series with the easily computable components.  Three examples are considered for the numerical illustrate and implementation of this method. Numerical Comparisons with respect to the analytical solutions have been considered . It is observed that the method is an alternative and efficient for finding the approximate solutions of the boundary values problems.